β-Amyloid Carrying the Dutch Mutation Has Diverse Effects on Calpain-Mediated Toxicity in Hippocampal Neurons - Nicholson, Alexandra M (ScholarOne, 2011)
Hereditary cerebral hemorrhage with amyloidosis–Dutch type is a disorder associated with a missense mutation (E693Q) in the β-amyloid (Aβ)-coding region of the amyloid precursor protein (APP). This familial disease is characterized by cognitive deficits secondary to intracerebral hemorrhage and, in some cases, progressive Alzheimer’s disease (AD)-like dementia. Although this mutation was the first ever reported in the human APP gene, little is known about the molecular mechanisms underlying the direct toxic effects of this mutated Aβ on central neurons. In the present study, we assessed the role of calpain-mediated toxicity in such effects using an AD primary culture model system. Our results showed that Dutch mutant Aβ (E22Q) induced calpain-mediated cleavage of dynamin 1 and a significant decrease in synaptic contacts in mature hippocampal cultures. These synaptic deficits were similar to those induced by wild-type (WT) Aβ. In contrast, calpain-mediated tau cleavage leading to the generation of a 17-kDa neurotoxic fragment, as well as neuronal death, were significantly reduced in E22Q Aβ–treated neurons when compared with WT Aβ–treated ones. This complex regulation of the calpain-mediated toxicity pathway by E22Q Aβ could have some bearing in the pathobiology of this familial AD form.